ASSESSING THE EFFECT OF COVID-19 ON TUBERCULOSIS TREATMENT OUTCOME IN ADAMAWA AND TARABA STATES, NORTH EASTERN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Tuberculosis is a common, and in many cases lethal, infectious disease caused by various strains of mycobacteria. Successes in treatment of tuberculosis lead to reduction in transmission, complications, and mortality among patients. The outbreak of COVID-19 drew the attention of governments and healthcare practitioners.  This study considers the effect of COVID-19 on Tuberculosis treatment. Data were sourced from Taraba and Adamawa States in North-east Nigeria. A total of 8820 patients’, records were used, with 3001 from Adamawa State and 5819 from Taraba State which involved TB patients’ records. At the bivariate level, the Pearson Chi-square test was employed to measure the association between the treatment outcome and the independent variables (local government area, treatment facility ownership, treatment regimen, patients’ supported, disease site, gender, HIV status and year of treatment). Thereafter multinomial Poisson regression analysis was performed on all statistically significant variables identified at the bivariate analysis. Decisions were taken based on p-value and odds ratios. The results of this study shows that the overall treatment success and cure rate across the States was on the average, 92.7% and 49.8% respectively. The highest treatment success rate of 94.5% was achieved in year 2021, while the year 2020 witnessed the highest cure rate of 53.5%. The overall cure rate of 49.8% is below the WHO recommendation. This study recommends that the non-pharmaceutical protocols to curtail the spread of COVID-19 should be strengthened in order to curtail TB spread, and that all TB patients should be tested for HIV.
Keywords: Tuberculosis; COVID-19; HIV; treatment outcome; North eastern Nigeria